DEVELOPMENT OF RIPPLE TANK TOWER TO INCREASE SCIENCE PROCESS SKILL PRINCIPLES IN MECHANICAL WAVE MATERIALS - MELLATI, DIAN; SUCAHYO, IMAM (Inovasi Pendidikan Fisika, 2018)
ABSTRACT This research aims to produce a worthy (valid, practical, and effective) ripple tank teaching aid to increase science process skills on the topic of mechanical wave. The methods in this research refer to ADDIE research model (Analysis, Design, Develop, Implementation, Evaluation). The developed teaching aid, was reviewed by two physics experts from The State University of Surabaya, then was validated by two lecturers from The State University of Surabaya and a physics teacher in SMA Muhammadiyah 1 Jombang. Based on the result of validation that has been done, the developed teaching aid is worth to use if it is viewed from validity aspect. To know its worth from effectiveness, restricted trial was conducted towards 30 students on grade XI MIA-1 in SMA Muhammadiyah 1 Jombang. Achieving effectiveness is viewed from skills aspect, skills aspect in this research is science process skill, using pre-test and post-test. Based on the pre-test and post-test analysis, it shows that the students science process skill is increasing. As for practical aspect, it was obtained by the students response questionnaire. Based on questionnaire analysis, it is known that the students response towards the teaching aid was positive and learning engagement was very good hence it can be stated that the developed teaching aid is worth to use from practical aspect. Keywords: Ripple tank teaching aid, The worth of teaching aid, Science process skills.